Islamic Educational Environment: A Conceptual Study On The Role Of Family, School, and Community - Nailah Meilindah; Syarifuddin Ondeng; Muhammad Yahdi (Journal Innovative Practices in Education (JIPE), 2025)
The Islamic educational environment plays a strategic role in shaping the personality, character, and religious beliefs of students. The educational environment is not only understood as the physical space where the learning process takes place, but also encompasses non-physical dimensions such as values, culture, traditions, and a religious atmosphere that influence the continuous development of individuals. This article aims to conceptually examine the concept of the Islamic educational environment and its various types based on the perspective of Islamic education. The study focuses on the concept of the three centres of education, namely the family environment, school or madrasah, and community. The family environment is understood as the main foundation in shaping children's morals and character, schools play a role as formal institutions that develop the intellectual, moral, and spiritual aspects of students, while the community becomes a social space for the actualisation of Islamic values in real life. The results of the study show that these three educational environments are closely related and must work together harmoniously so that the objectives of Islamic education can be achieved optimally. A conducive and religious Islamic educational environment is expected to produce a generation that is faithful, knowledgeable, noble in character, and responsible in social life.